Induction of labour indications and timing: A systematic analysis of clinical guidelines. Issue 3 (May 2020) - Coates, Dominiek; Homer, Caroline; Wilson, Alyssa; Deady, Louise; Mason, Elizabeth; Foureur, Maralyn; Henry, Amanda
Abstract: Background: There is widespread and some unexplained variation in induction of labour rates between hospitals. Some practice variation may stem from variability in clinical guidelines. This review aimed to identify to what extent induction of labour guidelines provide consistent recommendations in relation to reasons for, and timing of, induction of labour and ascertain whether inconsistencies can be explained by variability guideline quality. Method: We conducted a systematic search of national and international English-language guidelines published between 2008 and 2018. General induction of labour guidelines and condition-specific guidelines containing induction of labour recommendations were searched. Guidelines were reviewed and extracted independently by two reviewers. Guideline quality was assessed using the Appraisal of Guidelines for Research and Evaluation II Instrument. Findings: Forty nine guidelines of varying quality were included. Indications where guidelines had mostly consistent advice included prolonged pregnancy (induction between 41 and 42 weeks), preterm premature rupture of membranes, and term preeclampsia (induction when preeclampsia diagnosed ≥37 weeks). Guidelines were also consistent in agreeing on decreased fetal movements and oligohydramnios as valid indications for induction, although timing recommendations were absent or inconsistent. Common indications where there was little consensus on validity and/or timing of induction included gestational diabetes, fetal macrosomia, elevated maternal body mass index, and twin pregnancy. Conclusion: Substantial variation in clinical practice guidelines for indications for induction exists. As guidelines rated of similar quality presented conflicting recommendations, guideline variability was not explained by guideline quality. Guideline variability may partly account for unexplained variation in induction of labour rates.